Pemanfaatan Alat Peraga Styrofoam dan Evaluasi Interaktif Bamboozle untuk Meningkatkan Pemahaman dan Motivasi Belajar Siswa melalui Model Pembelajaran Berbasis Proyek di Kelas VI Sekolah Dasar Negeri 060875 Medan - Siregar, Sunarsini; Pratiwi, Indah; Nurkartika, Nurkartika (Medan Resource Center, 2025)
This study investigates the effectiveness of integrating styrofoam-based teaching aids and the interactive digital evaluation tool Bamboozle to enhance students’ understanding and motivation in learning the Solar System through the Project-Based Learning (PjBL) model. Conducted as Classroom Action Research in two cycles at Grade VI of Sekolah Dasar Negeri 060875 Medan, the study aims to address low student engagement and limited conceptual comprehension in science education. Data collection included pretests, posttests, observation sheets, and documentation. The findings reveal a significant improvement in students’ academic performance, with average scores increasing from 52.43 to 85.71 and a gain score of 0.705, indicating a high level of learning progress. Additionally, students demonstrated heightened motivation, actively participating in project creation, group discussions, and digital quizzes via Bamboozle. The study concludes that combining tangible teaching aids with digital evaluation platforms within the PjBL framework not only reinforces conceptual understanding but also cultivates student enthusiasm and involvement. This approach offers a promising pedagogical strategy for improving learning outcomes in primary science education.